Pengaruh Cita Rasa Dan Harga Terhadap Kepuasan Konsumen Membeli Rokok Di Tobacco House Lombok - Lalu Gagarin; Akhmad Saufi; Handry Sudiarta (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of taste and price on consumer satisfaction in buying cigarettes at Tobacco House Lombok. The population of this study were consumers who had purchased cigarettes at the Lombok Tobacco House. The data collection method uses a survey research method. Data collection techniques use questionnaires and online surveys with data collection tools, namely questionnaires. In addition, this study used a sample of 100 people with a purposive sampling method. This type of research is causal associative. Data processing in this study used SPSS 24.0 for Windows. The results of this study indicate that taste (X1) has a positive and significant effect on consumer satisfaction (Y ) with a t-test value of 2,614 and is at a significance of 0.010 and the results of the regression test are 24.4 and price (X2) has a significant positive effect on consumer satisfaction (Y) with a t-test value of 3.482 and a significance of 0.001 and a regression test result of 27.0.